Evaluation of pulmonary hypertension and clinical status in dogs with heartworm by Right Pulmonary Artery Distensibility Index and other echocardiographic parameters - Serrano-Parreño, B. (Parasit Vectors, 2017)
BACKGROUND: Pulmonary hypertension (PH) is a frequent and severe phenomenon in heartworm disease caused by Dirofilaria immitis, mainly caused by intimal proliferation of the arteries and pulmonary thromboembolisms. Transthoracic echocardiography is the method of choice for diagnosing PH in dogs although the diagnosis is often based on indirect and subjective parameters. The Right Pulmonary Artery Distensibility Index (RPAD Index) is a method that has been recently validated to estimate the presence and severity of PH in heartworm-infected dogs. This study compared some echocardiographic parameters commonly used to estimate PH in 93 dogs infected by D. immitis and evaluated the impact of the parasite burden, microfilaremia, sex or origin of the dog (client-owned/shelter). RESULTS: None of the studied echocardiographic variables seemed useful in the estimation of the evaluated clinical aspects, except for the PA/Ao ratio for parasite burden. The RPAD Index was determined in 88 of the dogs; of these, 70.4% had PH (mild: 37.5%, moderate: 19.3%, severe: 13.6%). This Index showed non-significant differences according to microfilaremia, sex, origin or parasite burden. Symptomatic dogs showed PH more often and displayed more severe PH, in addition the presence of symptoms was greater among dogs with high burden; on the other hand 64.4% of asymptomatic dogs had some degree of PH according to the RPAD Index. Apart from the PA/Ao ratio, the other evaluated echocardiographic variables were not useful in evaluating of the hypertensive status of the heartworm-infected dog compared to the RPAD Index. CONCLUSIONS: The estimation of most common indirect parameters is not useful in predicting PH in heartworm-infected dogs. The results confirm the RPAD Index as an objective and supportive test in the monitoring and evaluation of PH in the heartworm-infected dog, and show a potential diagnostic value for the detection of PH in asymptomatic animals.